Budesonide promotes airway epithelial barrier integrity following double-stranded RNA challenge. - Clara Rimmer; Savas Hetelekides; Sophia I Eliseeva; Steve N Georas; Janelle M Veazey (PLoS ONE)
Airway epithelial barrier dysfunction is increasingly recognized as a key feature of asthma and other lung diseases. Respiratory viruses are responsible for a large fraction of asthma exacerbations, and are particularly potent at disrupting epithelial barrier function through pattern recognition receptor engagement leading to tight junction dysfunction. Although different mechanisms of barrier dysfunction have been described, relatively little is known about whether barrier integrity can be promoted to limit disease. Here, we tested three classes of drugs commonly prescribed to treat asthma for their ability to promote barrier function using a cell culture model of virus-induced airway epithelial barrier disruption. Specifically, we studied the corticosteroid budesonide, the long acting beta-agonist formoterol, and the leukotriene receptor antagonist montelukast for their ability to promote barrier integrity of a monolayer of human bronchial epithelial cells (16HBE) before exposure to the viral mimetic double-stranded RNA. Of the three, only budesonide treatment limited transepithelial electrical resistance and small molecule permeability (4 kDa FITC-dextran flux). Next, we used a mouse model of acute dsRNA challenge that induces transient epithelial barrier disruption in vivo, and studied the effects budesonide when administered prophylactically or therapeutically. We found that budesonide similarly protected against dsRNA-induced airway barrier disruption in the lung, independently of its effects on airway inflammation. Taken together, these data suggest that an under-appreciated effect of inhaled budesonide is to maintain or promote airway epithelial barrier integrity during respiratory viral infections.